Lord and Lady Bunny -- almost royalty! - Horvath, Polly (Schwartz & Wade books, 2014)
"Madeleine and her hippie parents travel to England to run a candy shop. Meanwhile Mr. and Mrs. Bunny also travel to England, where Mrs. Bunny tries to weasel her way into the ranks of royalty"--